Comparing diabetic retinopathy lesions in scanning laser ophthalmoscopy and colour fundus photography. Issue 8 (8th July 2019) - Nghiem, Allan Zhifa; Nderitu, Paul; Lukic, Marko; Khatun, Mumina; Largan, Ross; Kortuem, Karsten; Balaskas, Konstantinos; Sim, Dawn
Abstract: Purpose: To evaluate the detection of different lesions of diabetic retinopathy (DR) in scanning laser ophthalmoscopy (SLO) compared to colour fundus photographs within the same retinal field. Methods: Scanning laser ophthalmoscopy and colour fundus photographs of 67 eyes taken on the same day of dilated patients with different grades of diabetic retinopathy were retrospectively examined. SLO images were then cropped to match the size and position of its 45‐degree colour fundus photograph equivalent. Five independent masked graders assessed the images. Features of DR including haemorrhages, microaneurysms, exudates, cotton wool spots, intraretinal microvascular abnormalities, venous beading and neovascularization were analysed. Additionally, each image was classified according to Early Treatment of Diabetic Retinopathy Study (ETDRS) grading and English Diabetic Eye Screening Programme (DESP) grading. Results: There was moderate to good agreement in ETDRS and DESP grading between SLO and colour fundus photographs within individual graders (weighted kappa range 0.45–0.65). The average number of microaneurysms for SLO and colour photographs showed a high degree of agreement (ICC: 0.92). Equally, the average number of blot haemorrhages in SLO and colour images showed strong agreement (ICC: 0.98) and the average number of cotton wool spots in SLO and colour images correlated well (ICC: 0.92). For these three lesions, the intergrader reliability was good (ICC ≥0.66) for both modalities. Conclusion: There was good correlation in detected microaneurysms, blot haemorrhages and cotton wool spots between SLO and colour fundus photographs. However, there was intergrader variability in flame haemorrhage, intraretinal microvascular abnormalities, venous beading and neovascularization grading with both modalities.